Analysis of the effect of calcination and substitution on the phase properties of strontium-hydroxyapatite - Putri, Elvina; Iwantono, Iwantono; Zulkarnain, Zulkarnain; Setiawan, Jan (Universitas Riau, 2024)
Hydroxyapatite (HAp) is a ceramic biomaterial that is highly biocompatible and employed in a variety of biomedical applications. Its chemical formula is Ca10(PO4)6(OH)2, comprising calcium and phosphate, the primary minerals found in bones and teeth. The precipitation method can be used to change the structure of hydroxyapatite by replacing strontium ions (Sr2+) with calcium ions (Ca2+). This work aims to determine the physical parameters of Sr-HAp samples with substitutions of 0, 0.25, 0.3, 0.5, and 0.75 %-mol. The samples were dried at 105ºC for four hours and then calcined at 750ºC for two hours. Sr-HAp samples were examined using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and SEM-EDX. The XRD data revealed diffraction patterns with distinctive peak intensities, lattice characteristics, and crystal structures. The XRD data revealed diffraction patterns with distinct peak intensities, lattice characteristics, and crystal structures modified by Sr replacement. The FTIR data revealed vibrations of the PO3-, Ca–O, Sr–O, and OH- functional groups, with differences in intensity and peak shifts caused by Sr substitution. SEM results revealed the shape of Sr-HAp particles in an agglomerated form, while EDX supplied elemental composition data through a comparison of O, P, Ca, and Sr atomic percentages. The study found that Sr substitution and calcination alter the structure, morphology, and bioactivity of Sr-HAp. Sr substitutions at 0% and 0.5% are remarkable in that they result in multiphases after calcination.